Genomic loci associated with grain yield under well-watered and water-stressed conditions in multiple bi-parental maize populations - Ndlovu, Noel; Gowda, Manje; Beyene, Yoseph; Chaikam, Vijay; Nzuve, Felister M.; Makumbi, Dan; McKeown, Peter C.; Spillane, Charles; Prasanna, Boddupalli M. (Frontiers in Sustainable Food Systems, 2024)
Smallholder maize farming systems in sub-Saharan Africa (SSA) are vulnerable to drought-31 induced yield losses, which significantly impact food security and livelihoods within these 32 communities. Mapping and characterizing genomic regions associated with water stress 33 tolerance in tropical maize is essential for future breeding initiatives targeting this region. In 34 this study, three biparental F3 populations composed of 753 families were evaluated in Kenya 35 and Zimbabwe and genotyped with high-density single nucleotide polymorphism (SNP) 36 markers. These genotypes were applied for quantitative trait loci (QTL) mapping of grain yield 37 (GY), plant height (PH), ear height (EH) and anthesis-silking interval (ASI) under well-watered 38 (WW) and water-stressed (WS) conditions. Across the studied maize populations, mean GY 39 exhibited a range of 4.55 -8.55 t/ha under WW and 1.29 -5.59 t/ha under WS, reflecting a 31 40 -59% reduction range under WS conditions. Genotypic and genotype-by-environment (G×E) 41 variances were significant for all traits except ASI. Overall broad sense heritabilities for GY 42 were low to high (0.25 -0.60). For GY, these genetic parameters were decreased under WS 43 conditions. Linkage mapping revealed a significant difference in the number of QTLs detected, 44 with 93 identified under WW conditions and 41 under WS conditions. These QTLs were 45 distributed across all maize chromosomes. For GY, eight and two major effect QTLs (>10% 46 phenotypic variation explained) were detected under WW and WS conditions, respectively. 47 Under WS conditions, Joint Linkage Association Mapping (JLAM) identified several QTLs 48 with minor effects for GY and revealed genomic region overlaps in the studied populations. 49Across the studied water regimes, five-fold cross-validation showed moderate to high 50 prediction accuracies (-0.15 -0.90) for GY and other agronomic traits. Our findings emphasize 51 the polygenic nature of WS tolerance and the immense potential of using genomic selection in 52 improving genetic gain in maize breeding.